Two new ant species (Formicidae: Dorylinae, Ponerinae) from New Caledonia - Ramage, Thibault; Jouault, Corentin; Schmidt, Alexander R.; Seyfullah, Leyla J.; Perrichot, Vincent (European Journal of Taxonomy, 2019)
Two new species of ants (Hymenoptera: Formicidae) collected from New Caledonia are described and figured based on worker specimens: Leptogenys loarelae Ramage sp. nov. (Ponerinae, Ponerini) and Lioponera neocaledonica Jouault, Ramage & Perrichot sp. nov. (Dorylinae, Cerapachyini). All specimens were collected from the South Province of Grande Terre. These two new species are primarily distinguished from the other New Caledonian relatives by the size and shape of petiole for L. loarelae Ramage sp. nov. and by the presence of dorsolateral margins on the mesosoma for L. neocaledonica Jouault, Ramage & Perrichot sp. nov. Keys to New Caledonian Leptogenys and Lioponera are provided.